Exploiting common aspects of obesity and cancer cachexia for future therapeutic strategies - Molocea, Claudia-Eveline; Tsokanos, Foivos Filippos; Herzig, Stephan (Current opinion in pharmacology, 2020)
Obesity and cancer cachexia are diseases at opposite ends of the BMI. However, despite the apparent dichotomy, these pathologies share some common underlying mechanisms that lead to profound metabolic perturbations. Insulin resistance, adipose tissue lipolysis, skeletal muscle atrophy and systemic inflammation are key players in both diseases. Several strategies for pharmacological treatments have been employed in obesity and cancer cachexia but demonstrated only limited effects. Therefore, there is still a need to develop novel, more effective strategies. In this review we summarize existing therapies and discuss potential novel strategies that could arise by bridging common aspects between obesity and cachexia. We discuss the potential role of macrophage manipulation and the modulation of inflammation by targeting Nuclear Receptors (NRs) as potential novel therapeutic strategies.